SUMBER TASAWUF, SYAHADAT, DAN IMPLIKASINYA DALAM PEMAKNAAN TERHADAP REALITAS - abdul wachid bambang suharto (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract: This research is motivated by the vital words of shahada and the cleanliness of the human heart or in Islamic mysticism that is called Sufism. Apart from Sufism, there are also terms “esotericism” and “spirituality” whose alignment of philosophies and concepts are often vague. Therefore, the purpose of this study is to identify the source of Sufism, the concept of the shahada, and the implications for the reality of life. The data source used is documentation through the process of reading, analyzing, observing, and describing information related to the object of research. The results of this study indicate that there are many meanings of the term Sufism, those are purified people, goat hair that Sufis commonly used as clothing, the name of a room near Medina, rows of saf when praying, and wisdom. The source of Sufism comes from Islamic values. Sufism is associated with awareness and feeling. Sufism is also related to Islamic morals. Therefore, the principal reference sources are al-Qur'an and as-Sunnah (Hadith). The reality in the perspective of Sufism is